2-[(E)-Benzyliminomethyl]-4-methylphenol - Liang, Qi-Feng (International Union of Crystallography, 2008)
In the title Schiff base, C(15)H(15)NO, the benzene rings form a dihedral angle of 74.91 (1)°. There is a strong intramolecular O—H⋯N hydrogen bond.